Big data storage configuration and performance evaluation utilizing NDAS storage systems. Issue 2 (1st August 2018) - Park, Jung Kyu; Kim, Jaeho
Abstract: Recently, a large amount of multimedia data is rapidly increasing due to cloud activation. For this reason, there is a need for a technique capable of handling large amounts of data and large storage devices. In this way, a network storage device such as a NAS or a SAN is used to configure a large-capacity storage device in a network environment. In this paper, a large capacity storage device is constructed by using network direct connection storage device. We performed benchmark experiments to verify the scalability of the constructed storage devices using network direct attached storage.